2008
DOI: 10.1128/jvi.01586-08
|View full text |Cite
|
Sign up to set email alerts
|

Bovine-Like Coronaviruses Isolated from Four Species of Captive Wild Ruminants Are Homologous to Bovine Coronaviruses, Based on Complete Genomic Sequences

Abstract: We sequenced and analyzed the full-length genomes of four coronaviruses (CoVs), each from a distinct wild-ruminant species in Ohio: sambar deer (Cervus unicolor), a waterbuck (Kobus ellipsiprymnus), a sable antelope (Hippotragus niger), and a white-tailed deer (Odocoileus virginianus). The fecal samples from the sambar deer, the waterbuck, and the white-tailed deer were collected during winter dysentery outbreaks and sporadic diarrhea cases in 1993 and 1994 (H. Tsunemitsu, Z. R. el-Kanawati, D. R. Smith, H. H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 69 publications
2
93
0
1
Order By: Relevance
“…Sequence analysis of the S and HE genes, however, indicated that the strains show a high similarity to BcoV. This was confirmed by phylogenetic analysis, thus supporting data obtained previously (Alekseev et al, 2008). The CoV strain isolated in this study appears to derive from the same ancestor as the BcoV 05/01 and BcoV 05/02 strains isolated from cattle in Korea.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Sequence analysis of the S and HE genes, however, indicated that the strains show a high similarity to BcoV. This was confirmed by phylogenetic analysis, thus supporting data obtained previously (Alekseev et al, 2008). The CoV strain isolated in this study appears to derive from the same ancestor as the BcoV 05/01 and BcoV 05/02 strains isolated from cattle in Korea.…”
Section: Resultssupporting
confidence: 90%
“…Also, the sequences of the S and HE genes of Korean CoV strains represented on the tree grouped according to year of isolation. These data support the hypothesis that genetic difference may be related more to the time of the appearance of an outbreak than to its geographic location (Alekseev et al, 2008;Jeong et al, 2005b). The 99.9% aa identity of the five bovine-like CoV strains suggests that the zoo ruminants were infected by the same [ ( F i g .…”
Section: Resultssupporting
confidence: 76%
“…However, as other genomic regions were not analysed in this study, a potential origin of strain 339/07-C as recombinant virus between BuCoV and BCoV cannot be ruled out definitively. The BCoV origin or, alternatively, the presence of a common ancestor, has been hypothesised for several group 2a CoVs, including HCoV-OC43 (Vijgen et al, 2005), PHEV (Vijgen et al, 2006), CRCoV (Erles et al, 2007;Lorusso et al, 2009) and some ruminant CoVs (Hasoksuz et al, 2007;Jin et al, 2007;Alekseev et al, 2008;Decaro et al, 2008d). We have already shown that more than one BCoV strain or ancestor virus was likely involved in the origin of CRCoV, thus leading to the emergence of different canine strains (Lorusso et al, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…Some coronaviruses appear to be generalists, capable of infecting many different orders of mammals. For example, Betacoronavirus 1 has been detected in dogs, humans, and numerous ungulate species (21)(22)(23). Other coronaviruses have been detected in only a single mammalian order, such as the many SARS-like coronaviruses that have been found only in bats (24,25).…”
Section: Coronavirus Host Range Expansionmentioning
confidence: 97%